Teachers’ attitudes towards integrating students with motor disabilities in the first three grades with ordinary students in schools Mafraq governorate (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
The aim of this research is to identify teachers' attitudes towards integrating children with motor disabilities in the first three grades with ordinary students in Mafraq governorate and its relationship to some variables represented by (gender, educational qualification, experience). To achieve the study's objectives, the survey method was used.  The study population consisted of all primary school teachers in Mafraq governorate, who numbered (1563) male and female teachers, of whom (291) were male and (1272) female teachers, according to the statistics of the Ministry of Education for the academic year 2020/2021, while the sample of the study consisted of (300) teachers.  And a female teacher, ie, 19% of the study population.  72 % The two researchers built a questionnaire to measure the attitudes of male and female teachers towards integrating students with motor disabilities with ordinary students in Mafraq Governorate. It consisted of (42) items distributed over five areas: social, academic, emotional, educational environment, and teacher competencies.  The study showed• Attitudes of the study sample towards integrating students with motor disabilities in regular public schools were positive.• There are statistically significant differences at the level of statistical significance (a = 0.05) due to the gender variable in favor of males, to the experience variable in favor of those with short experience (1-5) years, and to the educational qualification variable in favor of the bachelor's degree.The researchers suggested the necessity of preparing teachers who study in basic schools, equipping schools with rooms of resources and teaching aids necessary for inclusion, educating and assisting students, and positively accepting people with motor disabilities.